Evaluation of mitigating measures in the attenuation of flooding events in the Botafogo Córrego basin, Goiânia, GO (Research, Society and Development, 2021)
The urban densification process associated with changes in the rain profile has resulted in extreme hydrological events, creating adverse situations for people who live or transit in densely urbanized watershed areas. In this sense, the objective was to propose and evaluate mitigating measures to mitigate the effects of intense rain in the hydrographic basin of the Botafogo stream in Goiânia. In the methodology a scenario was adopted of 15% of the area of ​​each lot destined for the infiltration process and another that considers the arrangement of retention basins in the flow lines of the highest flow. A relation was considered between the average of the maximum intensities of precipitation, the conditions of coverage and use, the morphometric characteristics of the basin and its resultant in peak flow in face of the maximum flow supported by the main channel. The results indicate that the maximum flow supported by the channel in the vicinity of its outlet is 26.51 m³ / s and that the 15% area of ​​each lot being used for the infiltration process would not be sufficient for the considerable attenuation, considering that would only result in a reduction from 62.27 m³ / s to 58.85 m³ / s. Finally, it is highlighted that one of the most recommended measures would be the construction of retention structures, which would work releasing only the flows that added together would not exceed the capacity of the main channel.